Collaborative mental health services in primary care systems in Latin America: contextualized evaluation needs and opportunities. (5th February 2015) - Sapag, Jaime C.; Rush, Brian; Ferris, Lorraine E.
Abstract: Aim: This study examined Latin American evaluation needs regarding the development of a collaborative mental health care (CMHC) evaluation framework as seen by local key health‐care leaders and professionals. Potential implementation challenges and opportunities were also identified. Methods: This multisite research study used an embedded mixed methods approach in three public health networks in Mexico, Nicaragua and Chile. Local stakeholders participated: decision‐makers in key informant interviews, front‐line clinicians in focus groups and other stakeholders through a survey. The analysis was conducted within site and then across sites. Results: A total of 22 semi‐structured interviews, three focus groups and 27 questionnaires (52% response rate) were conducted. Participants recognized a strong need to evaluate different areas of CMHC in Latin America, including access, types and quality of services, human resources and outcomes related to mental disorders, including addiction. A priority was to evaluate collaboration within the health system, including the referral system. Issues of feasibility, including the weaknesses of information systems, were also identified. Conclusion: Local stakeholders strongly supported the development of a comprehensive evaluation framework for CMHC in Latin America and cited several dimensions and contextual factors critical for inclusion. Implementation must allow flexibility and adaptation to the local context.